Induction of immunity and tolerance in vitro by hapten protein conjugates. 3. Hapten inhibition studies of antigen binding to B cells in immunity and tolerance. - Feldmann, M (1972)
The capacity of dissociated spleen cell suspensions to be immunized by dinitrophenylated polymeric flagellin (DNP POL), in the absence of thymus-dependent lymphocytes or macrophages, provided a simple experimental system to investigate the mechanism of binding of antigen molecules to nonthymus-dependent lymphocyte (B cell) receptors during the induction of immunity or tolerance. Various nonimmunogenic DNP compounds were used to inhibit the anti-DNP response to DNP POL. By performing inhibition experiments of brief duration at 4 degrees C, it was established that the inhibition of the anti-DNP response by nonimmunogenic compounds was due to competitive blockade of receptors, and not tolerance or receptor modulation. It was found that univalent DNP compounds were much less efficient inhibitors of the antibody response than multivalent DNP conjugates. The difference in inhibitory capacity between univalent and multivalent DNP human globulin (DNP HgG) suggested the importance of interaction with both combining sites of a single receptor antibody molecule. Nonimmunogenic highly conjugated DNP(3)POL was a more efficient inhibitor of the anti-DNP response to immunogenic DNP(1)POL than DNP(12)HgG, indicating that interactions at more than one receptor molecule are involved in immunization of B cells. Recent demonstrations of the rapid metabolic turnover of receptor antibody molecules suggests that the requirement for multipoint binding (to different receptors) may simply be to maintain the antigen at the cell surface in a dynamic system. Competitive inhibition experiments were also performed to investigate the mechanism of binding of DNP(3)POL in the induction of B cell tolerance. It was found that monovalent DNP compounds or multivalent DNP(12)HgG did not prevent the induction of tolerance, unlike their capacity to inhibit immunity, suggesting that a tolerance-inducing antigen binds more avidly to the cell membrane than an immunogen. The inhibition data obtained here, together with prior results describing the differential immunogenicity of DNP conjugates of different structure, and the importance of epitope density on DNP POL conjugates, permit certain conclusions about the details of antigen-receptor interaction in immunity and tolerance. Distinctions between the mechanisms of immune and tolerance induction are discussed.